2011
DOI: 10.1142/s0219686711002211
|View full text |Cite
|
Sign up to set email alerts
|

Machined Surface Error Analysis — A Face Milling Approach

Abstract: In the automotive industry, sealing quality between two flat joint surfaces is directly affected by the surface flatness. To know how much flatness is caused by machining operations, a traditional trial-and-error method has been used. The prediction for machined surface error/distortion can help to assess the integrity of the structural design as well as develop fixturing scheme to optimize machining quality. In this paper, a finite element method is applied to extract the compliance matrix of milling surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Effect of Work-piece Feed Direction. In the face milling process, the angle between the tooth and the work-piece feed direction keeps changing, cutting force is also changing in the tangential and radial force components, different feed marks on the milled work-piece surface will be generated [8].When the tooth parallel to the feed direction of work-piece, the surface roughness value is the maximum. Therefore, static prediction model of surface roughness should be based on the direction of the maximum value.…”
Section: Fig 1 Face Milling Systemmentioning
confidence: 99%
“…Effect of Work-piece Feed Direction. In the face milling process, the angle between the tooth and the work-piece feed direction keeps changing, cutting force is also changing in the tangential and radial force components, different feed marks on the milled work-piece surface will be generated [8].When the tooth parallel to the feed direction of work-piece, the surface roughness value is the maximum. Therefore, static prediction model of surface roughness should be based on the direction of the maximum value.…”
Section: Fig 1 Face Milling Systemmentioning
confidence: 99%
“…There are very few literature prediction models for surface flatness obtained by face milling, for example, among them (Gu et al 1997a, b;Liu and Zou 2011;Yi et al 2015). Gu et al (1997a, b) showed in their work a model of plane prediction for face milling operations, taking into account cutting conditions, elastic deformations of the spindle milling cutter and workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al (1997a, b) showed in their work a model of plane prediction for face milling operations, taking into account cutting conditions, elastic deformations of the spindle milling cutter and workpiece. Liu and Zou (2011) predicted surface flatness errors in face milling using the traditional method. The work combines the empirical data and simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…But measurement of flatness error using elastic deformation and spindle axis tilt could be inflated by inclusion of surface roughness. Liu and Zou [29] predicted the surface flatness errors in the course of face milling, using the traditional trial-and-error method. Their work emphasized on the optimization of machining parameters to minimize surface deformation under machining loads.…”
Section: Introductionmentioning
confidence: 99%